Identifying the Suitability of Warm Mix Asphalt for Reducing the Production Temperatures of Crumb Rubber-Modified Asphalt Mixtures: Economic and Environmental Perspective - Wagh V.P.; Kumar S.; Gupta A. (My University, 2025)
The higher production temperature and greenhouse gas emissions restrain the use of crumb rubber (CR) obtained from recycled tires in pavement construction. Warm mix asphalt (WMA) technology is a sustainable solution for crumb rubber-modified bitumen (CRMB) as it allows the production of asphalt mixtures at lower temperatures. In addition, WMA lowers fuel consumption and greenhouse gas (GHG) emissions, leading to the cleaner production of asphalt mixtures. The primary objective of the study is to minimize the production temperature of crumb rubber-modified (CRM) binders with the use of WMA technology. This study explores the mixing and compaction temperatures using a workability approach. The study found that the conventional viscous-based methods do not yield appropriate production temperatures for CRM asphalt binders. The workability approach used in this study was able to quantify the mixing and compaction temperatures for different CRM mixture incorporated with WMA technologies. About 4%-13% and 5%-22% reduction in mixing and compaction temperatures, respectively, were obtained for different WMA technologies. Finally, the reduction in GHG and energy consumption were studied for WMA technology at their reduced mixing and compaction temperature. The use of WMA technology reduced the energy consumption by around 4%-12% and GHG emissions by 4%-13% relative to base CRM mixture. The amount of reduction in emission and energy consumption was found to be the function of fuel type, WMA additives, and their respective dosages. © 2024 American Society of Civil Engineers.